Brain-Wide Mapping of Afferent Inputs to Accumbens Nucleus Core Subdomains and Accumbens Nucleus Subnuclei - Ma, Liping; Chen, Wenqi; Yu, Danfang; Han, Yunyun (Frontiers in Systems Neuroscience, 2020)
The nucleus accumbens (NAc) is the ventral part of the striatum and the interface between cognition, emotion, and action. It is composed of three major subnuclei: i.e., NAc core (NAcC), lateral shell (NAcLS), and medial shell (NAcMS), which exhibit functional heterogeneity. Thus, determining the synaptic inputs of the subnuclei and subdomains of the NAc is important for understanding the circuit mechanisms involved in regulating different functions. Here, we simultaneously labeled subregions of the NAc with cholera toxin subunit B conjugated with multicolor Alexa Fluor, then imaged serial sections of the whole brain with a fully automated slide scanning system. Using the interactive WholeBrain framework, we characterized brain-wide inputs to the NAcC subdomains, including the rostral, caudal, dorsal, and ventral subdomains (i.e., rNAcC, cNAcC, dNAcC, and vNAcC, respectively) and the NAc subnuclei. We found diverse brain regions, distributed from the cerebrum to brain stem, projection to the NAc. Of the 57 brain regions projection to the NAcC, the anterior olfactory nucleus exhibited the greatest afferent input contribution. For brain-wide input patterns, the rNAcC and cNAcC had the same upstream brain regions but different projection neuron populations of almost equal proportions, whereas the dNAcC and vNAcC showed the same upstream brain regions but with slight differences in projection proportions. Of the 55 brain regions projection to the NAcLS, the piriform area contributed most of the afferent inputs. Of the 72 brain regions projection to the NAcMS, the lateral septal nucleus contributed most of the afferent inputs. For brain-wide input patterns of NAc subnuclei, the NAcC and NAcLSh received different inputs from similar upstream brain regions, whereas the NAcMS exhibited distinct upstream brain regions. Thus, the NAcC subdomains appeared to share the same upstream brain regions, although with different projection neuron populations and proportions, whereas the NAc subnuclei received distinct inputs from multiple upstream brain regions. These results lay an anatomical foundation for understanding the afferent input patterns of NAcC subdomains and NAc subnuclei and the functional differences among them.